2020
DOI: 10.15252/embj.2020106696
|View full text |Cite
|
Sign up to set email alerts
|

A stress‐induced tyrosine‐tRNA depletion response mediates codon‐based translational repression and growth suppression

Abstract: Eukaryotic transfer RNAs can become selectively fragmented upon various stresses, generating tRNA‐derived small RNA fragments. Such fragmentation has been reported to impact a small fraction of the tRNA pool and thus presumed to not directly impact translation. We report that oxidative stress can rapidly generate tyrosine‐tRNAGUA fragments in human cells—causing significant depletion of the precursor tRNA. Tyrosine‐tRNAGUA depletion impaired translation of growth and metabolic genes enriched in cognate tyrosin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 82 publications
(119 reference statements)
0
19
1
Order By: Relevance
“…In conclusion, the recent study by Huh et al (2020) GUA competes for hnRNPA1 binding with specific growth-associated mRNA subsets promoting their destabilization. Right, pre-tRNA Tyr GUA fragmentation subsequently depletes mature tRNA Tyr GUA , thereby hampering the translation of growth-related mRNAs (e.g., USP3, EPCAM, and SCD) that are enriched in tyrosine codons.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In conclusion, the recent study by Huh et al (2020) GUA competes for hnRNPA1 binding with specific growth-associated mRNA subsets promoting their destabilization. Right, pre-tRNA Tyr GUA fragmentation subsequently depletes mature tRNA Tyr GUA , thereby hampering the translation of growth-related mRNAs (e.g., USP3, EPCAM, and SCD) that are enriched in tyrosine codons.…”
mentioning
confidence: 75%
“…However, whether dynamic changes in tRNAs and tRNA-derived fragments actively contribute to gene regulation remains debated. In this issue, Huh et al (2020) highlight tyrosine tRNA GUA fragmentation at the nexus of an evolutionarily conserved adaptive codonbased stress response that fine-tunes translation to restrain growth in human cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One year later, another study published in the same journal showed that abnormally expressed tRF-related mRNAs were also correlated with glycolysis and ATP synthesis in almost all solid tumor types [ 84 ]. Moreover, other studies have also suggested the role of tRFs in protein biosynthesis in normal or tumor cells [ 32 , 85 ].…”
Section: Tsrnas and Cancer Hallmarksmentioning
confidence: 99%
“…Both pre-tRNAs and mature tRNAs can be fragmented in concert with tRNA expression, or in response to a stress stimulus (53)(54)(55)(56). While the nomenclature of tRFs is not yet well established, six main classes of tRFs have been described.…”
Section: Trf Synthesismentioning
confidence: 99%